2009
DOI: 10.1108/17504970910967564
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual collective online reflection in multicultural education classes

Abstract: PurposeThe purpose of the paper is to demonstrate how collective conceptual reflections facilitated by online blogs can promote pre‐service teachers' growth in multicultural education classes.Design/methodology/approachAnalysis of one blog is used to demonstrate how information gained through that triggered the instructor's informed reflection and guided subsequent in‐class teaching/learning.FindingsThrough the analysis of the demonstrative blog, it becomes apparent that while pre‐service teachers were appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In relation to assessment, the researchers of this study found it important, although originally unplanned, to measure both declarative and procedural knowledge to assess the academic and practical outcomes of students. This distinction between vocabulary and ability to express or demonstrate deeper conceptual understanding was also found by Oikonomidoy's (2009) study of preservice teacher narratives written for a multicultural education class.…”
Section: Discussionsupporting
confidence: 59%
“…In relation to assessment, the researchers of this study found it important, although originally unplanned, to measure both declarative and procedural knowledge to assess the academic and practical outcomes of students. This distinction between vocabulary and ability to express or demonstrate deeper conceptual understanding was also found by Oikonomidoy's (2009) study of preservice teacher narratives written for a multicultural education class.…”
Section: Discussionsupporting
confidence: 59%
“…Land (2000) concluded that these learning tools often failed to live up to expectations, due to a misunderstanding of the cognitive requirement for students to engage in the task. Similarly, Oikonomidoy (2009) found that the narratives employed in a blog by pre-service teachers were superficial and oversimplified. Xie et al (2008) showed that blogging was associated with an increase in student's reflective learning level, but that the increases were smaller for those who gave and received peer feedback.…”
Section: The Effect Of Blogs On Student Learning Outcomesmentioning
confidence: 98%
“…Teachers, regardless of their background, they have to try to place themselves in the diversity class by recognizing students more deeply and having attitudes and behaviors that value, not discriminate and discriminate, and provide fair services as a form of a democratic society to help students develop and improve ability to achieve educational success ability to achieve educational success [23,28]. The teacher in its implementation also needs to make learning that is culturally responsive by considering several ways of learning [29]. Teachers' understanding of diversity is expected to encourage tolerance in multicultural classes.…”
Section: Promoting Tolerance In the Multicultural Classroomsmentioning
confidence: 99%